The Effectiveness of Marketing Mix Strategies on Competitiveness: A Case of Food Micro and Small Enterprises in Masvingo, Zimbabwe. - Mutsikiwa, Munyaradzi; Basera, Clay Hutama; Dhliwayo, Kossam; Muzangwa, Jonatan (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2007)
The study seeks to investigate how Food Micro and Small Enterprises (FMSEs) (particularly restaurants) employ the 7Ps marketing mix strategy framework to enhance competitiveness measured in terms of patronage. The major emphasis is centred on the synergistic contribution of product, price, place, promotion, physical evidence, people, and process to enhancing competitive advantage to the enterprise. The researchers adopt a descriptive survey research design which enables them to establish consumers propensity to frequent the FMSE outlets. The sample size includes 95 regular customers and 20 people from management. The major findings of this research indicates that, the application of the 7ps framework plays an insignificant role in enhancing competitiveness serve for product and place variables